TINDAK PIDANA RAHASIA DAGANG DITINJAU DARI UU NO. 30 TAHUN 2000 TENTANG RAHASIA DAGANG - Muhammad Irkham Firdaus; Fajar Satriyawan Wahyudi (Law Department Jenderal Achmad Yani University, 2022)
Legal protection applies to the rights of every citizen, both to rights obtained due to transfer or rights arising from the results of their own copyrighted work. For rights in the form of copyrighted works, in the legal world they are included in the category of Intellectual Property Rights (IPR). Trade secrets as part of the Intellectual Property Rights system are not given much attention by the wider community, therefore they should be given protection like other Intellectual Property Rights objects. The purpose of this research is to find out criminal acts against violators of trade secrets and analyze using Law No. 30 of 2000. This research method uses normative research with a qualitative approach. The legal materials used in this study are primary legal materials and secondary legal materials. The primary legal material is the legislation in the field of intellectual property rights in Indonesia, namely Law no. 30 of 2000. Secondary legal materials used in this research are legal publications such as books, research results and so on. The results of this study indicate that anyone who intentionally and without rights uses or discloses a Trade Secret, or reneges on an agreement to maintain a Trade Secret or obtains or controls a Trade Secret in a way that is contrary to the applicable laws and regulations: shall be sentenced to a maximum imprisonment of 2 (two) years and/or a maximum fine of Rp.300,000,000.00 (three hundred million rupiah).